Validity and Reliability of The Verbal Descriptive Scale in Non-Myogenic Low Back Pain Patients - Salatina, Alfi; Komalasari, Dwi Rosella (Academic Physiotherapy Conference Proceeding, 2024)
Introduction: Pain is the most common problem in patients with low back pain (LBP) non-myogenic. There are many tools to measure pain, one of which is the Verbal Descriptive Scale (VDS). It needs validity and reliability to evaluate pain in patients with non-myogenic LBP. Therefore, this study aimed to determine the validity and reliability of VDS to evaluate pain in patients with non-myogenic LBP. Method: This research was an observational study method with a methodological research approach and a purposive sampling technique. The total sample was 55 people. Results: The validity of VDS showed well with p<0.001 and r calculated was higher than 0.9. Intra-rater and inter-rater reliability of VDS revealed excellent with Cronbach Alpha and Intra Class Correlation were more than 0.9 and p<0.05. While the SEM=0.068 and MDC=0.188. Conclusion: The VDS was valid and reliable for measuring pain in patients with non-myogenic low back pain.